Flubendazole induces mitotic catastrophe and senescence in colon cancer cells in vitro. (4th January 2016) - Králová, Věra; Hanušová, Veronika; Rudolf, Emil; Čáňová, Kristýna; Skálová, Lenka
Abstract: Objectives: Flubendazole (FLU), a member of benzimidazole family of anthelmintic drugs, is able to inhibit proliferation of various cancer cells. The aim of present study was to elucidate the mechanisms of antiproliferative effect of FLU on colorectal cancer cells in vitro . Methods: The effect of FLU on proliferation, microtubular network, DNA content, caspase activation and senescence induction was studied in SW480 and SW620 cell lines. Key findings: Flubendazole significantly affected cell proliferation in a pattern typical for mitotic inhibitor. This was accompanied by decrease in cyclin D1 levels, increase in cyclin B1 levels, activation of caspase 2 and caspase 3/7 and PARP cleavage. Morphological observations revealed disruption of microtubular network, irregular mitotic spindles, formation of giant multinucleated cells and increase in nuclear area and DNA content. In SW620 cell line, 37.5% giant multinucleated cells induced by FLU treatment showed positivity for SA-β-galactosidase staining. Cell lines were able to recover from the treatment and this process was faster in SW480 cells. Conclusion: Flubendazole in low concentration temporarily inhibits cell proliferation and induces mitotic catastrophe and premature senescence in human colon cancer cells in vitro .